A Study of Depression Among Aged in Surat City - Vishal Jariwala; R K Bansal; Swati Patel; Bimal Tamakuwala (Medsci Publications, 2010)
This cross-sectional study interviews 105 elderly belonging to different socioeconomic and varying demographic groups of Surat city as per predefined inclusion and exclusion criteria with their informed consent in compliance with 'Ethical principles for medical research involving human subjects' of Helsinki Declaration, employing a probability sample technique. The data was analyzed using SPSS-15 and the results were recorded as frequencies, means ± standard deviations and p-values. Tables and figures were used for comprehensive viewing of the results. Chi-square test was used for categorical variables. A p-value of <0.05 was taken as the criteria of significance. The study explores depression and important correlates thereof.